Cytoplasmic male sterility and prospects for its utilization in breeding, genetic studies and seed production of potato - I. N. Anisimova; T. A. Gavrilenko (Вавиловский журнал генетики и селекции, 2017)
Increasing interest to cytoplasmic male sterility (CMS) and searching for restoration of pollen fertility (Rf) genes in potato is determined by a new way in the modern breeding of this important crop, the development of heterotic hybrids obtained after crosses of inbred diploid lines. The paper reviews the main results of studies on CMS-Rf genetic systems in different species of cultivated plants, the modern methods and approaches of investigating molecular mechanisms of CMS and pollen fertility restoration, and also the available literature data on the status of these studies in potato. The nature of chimeric mitochondrial genes accounting for cytoplasmic male sterility is considered; the peculiarities of the structure and functions of restoration of pollen fertility genes are discussed; examples of CMS-Rf genetic systems in cultivated plant species including representatives of the family Solanaceae are presented. The main results of research on molecular mechanisms of CMS and fertility restoration obtained in the post-genomic era for various plant species using methods of transcriptomic and proteomic analyses are provided. As in many plant species, cytoplasmic male sterility in potato is of hybrid origin. The results of investigating genetic control of male sterility in potato are presented that have been carried out using conventional approaches (hybridological analysis) and led to the formation of the concept of genic cytoplasmic male sterility in some species of section Petota of the genus Solanum. The characteristics of potato cytoplasms types which are associated with male sterility are given. According to classification of Hosaka, Sanetomo (2012), these types include: T/beta, W/gamma and D, each distinguished by the phenotypic appearance of male sterility traits and also by the frequency of occurrence in the breeding varieties gene pool and in various potato species. The results of studies on developing DNA markers for identification of various potato cytoplasm types are presented.